2002
DOI: 10.1172/jci14270
|View full text |Cite
|
Sign up to set email alerts
|

Role of sarcolemmal KATP channels in cardioprotection against ischemia/reperfusion injury in mice

Abstract: IntroductionBrief periods of ischemia that precede sustained ischemia lead to a reduction of infarct size (1-4). This phenomenon is known as ischemic preconditioning (IPC) and the mechanisms underlying it remain unclear, despite extensive study (5-7). Sarcolemmal ATP-sensitive potassium (sarcK ATP ) channels were proposed to play an important role in the cardioprotective effect, because potassium channel openers (KCOs) mimicked the cardioprotection and the K ATP channel blocker glibenclamide abolished the IPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(161 citation statements)
references
References 48 publications
11
148
1
1
Order By: Relevance
“…These fi ndings have led to a widespread opinion that the cardioprotective effects of preconditioning are dependent on the opening of the mitoK ATP channel. However, the results of more recent studies suggest that the potential involvement of sarcK ATP channels in cardioprotection should not be ignored [49,64,65].…”
Section: Sarcolemmal K Atp Channelsmentioning
confidence: 99%
“…These fi ndings have led to a widespread opinion that the cardioprotective effects of preconditioning are dependent on the opening of the mitoK ATP channel. However, the results of more recent studies suggest that the potential involvement of sarcK ATP channels in cardioprotection should not be ignored [49,64,65].…”
Section: Sarcolemmal K Atp Channelsmentioning
confidence: 99%
“…Toyoda et al [13] found that while glibenclamide blocked IPC protection measured both from infarct size and recovery of contractile function, 5-HD affected only infarct size and HMR 1883 only functional recovery. Finally, strong evidence for a major role of sarcoK ATP in the mouse heart has come from knockout of its pore-forming subunit Kir6.2, which abolishes the protective effect of IPC [14].…”
Section: Introductionmentioning
confidence: 99%
“…Blockage of cardiac K ATP channels impairs ischemic preconditioning and extends infarction areas [46]. Thus, cardiac K ATP channels are considered to represent an endogenous cardioprotective mechanism usually attributed to SUR2A/Kir6.2-containing channels [47].…”
Section: Sur1d2 Functionally Displaces High-affinity Sulfonylurea Actionmentioning
confidence: 99%